PEMIMPIN MOBILISATOR - H. Abdullah Syarif (STAI Hubbulwathan Duri, 2016)
Every human being is a holder of responsibility. A man as leader often forgot his duty. The current conditions not only shows the weakness of the mentality of leaders in various level of office, but the societies are unruly also adds the problem. A leader is not just enough to know a solution of a problem, but the idea that solution must be applied to the problems. The characteristics of a mobilizing leader are a quick job completed with satisfactory results, efficient and effective, able to communicate, exemplary, and able in giving motivation.